An Alternative Proof of Rubin’s Lemma - Ghimire, Santosh (Nepal Journal of Mathematical Sciences, 2020)
Rubin's Lemma is an inhomogenous type inequality which is satisfied by the sequence of dyadic martingales. In this paper, we give a proof using the measure theoretic approach which is simpler and different than the original probabilistic approach.